Occupational burnout following the first wave of coronavirus disease at a Welsh district general hospital. (August 2022) - Srinivas, Gayathri Chinnappa; Whitham, Anwen; Rouse, Rachel; Hamlyn, Vincent; Williams, Matthew
A survey was conducted to identify the prevalence of occupational burnout amongst health care professionals caring for COVID-19 patients in the Intensive Care Unit (ICU) of a Welsh hospital. The response rate was 79%. Nurses and other staff reassigned to work in the ICU had higher levels of burnout. Working in Personal Protective Equipment was most distressing, followed by direct patient care. There were positive outcomes including learning opportunities, professional development and job satisfaction. The impact of the pandemic on staff burnout may have been mitigated by acknowledging the contribution of staff, improving communication and encouraging them to access support.